Challenges and opportunities related to the use of innovative modelling approaches and tools for microbiological food safety management. (June 2022) - Allende, Ana; Bover-Cid, Sara; Fernández, Pablo S
Abstract : Modelling in food microbiology has become an indispensable approach in food safety to generate predictions about the microbial behaviour. One of its weaknesses is the lack of reliable and relevant data for mathematical modelling. The increasing amounts of data and innovative modelling tools have the potential to provide relevant information on hazard, exposure, and surveillance reports. They can be combined to reduce the time needed to perform a risk assessment, improving food safety management decisions. Future tools will follow a multidisciplinary scope of action, including food microbiology, process engineering and technology, innovative mathematical modelling approaches, holistic perspective in risk assessment and multicriteria analysis beyond the health impact (risks–benefits) to provide appropriate risk mitigation and control options. When predictive modelling is used to establish risk management strategies able to reduce food safety risks, uncertainty analysis and communication are needed to provide a transparent answer indicating the limitations of the outcome.